1972
DOI: 10.1128/jvi.9.5.752-757.1972
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Bacteriophage P22 Infection on Host Cell Deoxyribonuclease Activity

Abstract: Infection of Salmonella typhimnurium with phage P22 causes a decrease in the activity of host deoxyribonuclease which degrades single-stranded deoxyribonucleic acid (DNA). This decrease is reversed when the infecting phage is P22c+; it is not-°o i reversed if the infecting phage kills the cell. The decrease does not occur in infections 4* with P22ts25.1 (which only adsorbs and injects DNA) or in infections of a lysogen by a nonvirulent phage. It does occur, however, after infections with other phages which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Specifically, bacteriophages lambda and T4 inactivate this enzyme in E. coli (38,40). Similarly, nuclease inactivation has also been demonstrated in Salmonella after infection with bacteriophage P22 (26). In Staphylococcus aureus (37), transformation requires lysogeny.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, bacteriophages lambda and T4 inactivate this enzyme in E. coli (38,40). Similarly, nuclease inactivation has also been demonstrated in Salmonella after infection with bacteriophage P22 (26). In Staphylococcus aureus (37), transformation requires lysogeny.…”
Section: Discussionmentioning
confidence: 93%
“…Co-infections showed that gp16 can work in trans, complementing a gp16-deficient particle, indicating that its essential early function occurs once DNA is ejected inside the host. Furthermore, gp16 deficient phage do not induce the superinfection exclusion response and gp16 is not part of the replication machinery [ 162 ]. Indirect evidence supports a membrane-breaching role, as purified gp16 disrupts dye-loaded, lipid vesicles [ 163 ].…”
Section: Bubblegrams and Cryo-et Reveal Asymmetrically Organized Pmentioning
confidence: 99%
“…Infections in the absence of functional P16. The following features of infection in the absence of functional P16 are well established: (i) adsorption proceeds with normal kinetics and (ii) phage DNA is at least partially released from the capsid; (iii) the host cells are not detectably affected; they continue to grow and divide with the same kinetics as uninfected cells (6; Hoffman, Ph.D. thesis); (iv) no change in the rate of DNA synthesis in the infected culture is observed, suggesting that no phage DNA is synthesized (6; Hoffman, Ph.D. thesis); (v) the parental phage DNA does not associate with the replication complex (23); (vi) these infections do not result in the transcription of any phage-specific RNA, as determined by RNA-DNA hybridization (E. N. Jackson, personal communication); (vii) superinfection exclusion is not induced; (viii) no phage protein synthesis is detected (15); (ix) two alterations in enzymatic activity are detected early in P22 infections-a loss of host DNase activity specific for denatured DNA (15) and an increase in phage-specified DNase activity specific for native DNA (36); infections in the absence of P16 activity fail to show either of these effects; and (x) the host cannot be lysogenized. Thus, in the absence of functional P16, there is a block at an early step in the infective process which prevents the expression of any phage functions following at least partial release of phage DNA from the capsid.…”
mentioning
confidence: 99%